Finite element electromagnetic field computation on the Sequent Symmetry 81 parallel computer - Hoole, S.R.H. (IEEE transactions on magnetics, 1990)
The fact that finite-element field analysis algorithms lend themselves ideally to parallelization is exploited to implement a finite-element analysis program for electromagnetic field computation on the Sequence Symmetry 81 parallel computer with three processors. Since in terms of waiting time, the maximum gains are to be made in matrix solution, special attention was given to parallelizing the solution part of the finite-element analysis. An outline of how parallelization could be exploited in most finite element operations is given, although the actual implementation of parallelism on the Sequent Symmetry 81 computer was in sparsity computation, matrix assembly, and the matrix solution areas. In all cases, the algorithms were modified to suit the parallel programming application rather than allowing the compiler to parallelize an existing algorithm.< >